Ant colony optimization for RDF chain queries for decision support - Hogenboom, Alexander; Frasincar, Flavius; Kaymak, Uzay (Expert systems with applications, 2013)
► We propose to optimize RDF chain query join order through ant colony optimization. ► We benchmark against existing two-phase optimization and genetic algorithm methods. ► For up to 15-join queries, our method excels in execution time and solution quality. ► A genetic algorithm executes faster for more joins, yet we excel in solution quality. Semantic Web technologies can be utilized in expert systems for decision support, allowing a user to explore in the decision making process numerous interconnected sources of data, commonly represented by means of the Resource Description Framework (RDF). In order to disclose the ever-growing amount of widely distributed RDF data to demanding users in real-time environments, fast RDF query engines are of paramount importance. A crucial task of such engines is to optimize the order in which partial results of a query are joined. Several soft computing techniques have already been proposed to address this problem, i.e., two-phase optimization (2PO) and a genetic algorithm (GA). We propose an alternative approach – an ant colony optimization (ACO) algorithm, which may be more suitable for a Semantic Web environment. Experimental results with respect to the optimization of RDF chain queries on a large RDF data source demonstrate that our approach outperforms both 2PO and a GA in terms of execution time and solution quality for queries consisting of up to 15 joins. For larger queries, both ACO and a GA may be preferable over 2PO, subject to a trade-off between execution time and solution quality. The GA yields relatively good solutions in a comparably short time frame, whereas ACO needs more time to converge to high-quality solutions.